2020
DOI: 10.48550/arxiv.2005.03934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monopole and dipole transitions of the cluster states of 18O

T. Baba,
M. Kimura

Abstract: On the basis of an extended antisymmetrized molecular dynamics calculation, we study the cluster structure and the of the 0 + and 1 − states of 18 O. We discuss that several different kinds of the cluster states appear in the excitation spectrum, and their monopole and dipole transitions are interesting fingerprints of unique cluster structure. We show that the monopole/dipole transitions are enhanced for the 14 C+α cluster states, while they are hindered for the molecular-orbit state.We also point out that th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…These transitions can populate the deep sub-barrier resonances and have unique selectivity for molecular states; hence, they are effective to identify the molecular states embedded in the continuum [38][39][40][41]. In particular, the method has already been successfully applied to the discussion of clustering and molecular states in many stable and unstable nuclei [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. On the same line of physics, Itoh et al [56] have measured the isoscalar transitions of 32 S, identified several excited states with enhanced transition strengths, and proposed a new band assignment for the α+ 28 Si and 16 O+ 16 O molecular states (and hence the superdeformed states of 32 S).…”
Section: Introductionmentioning
confidence: 99%
“…These transitions can populate the deep sub-barrier resonances and have unique selectivity for molecular states; hence, they are effective to identify the molecular states embedded in the continuum [38][39][40][41]. In particular, the method has already been successfully applied to the discussion of clustering and molecular states in many stable and unstable nuclei [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. On the same line of physics, Itoh et al [56] have measured the isoscalar transitions of 32 S, identified several excited states with enhanced transition strengths, and proposed a new band assignment for the α+ 28 Si and 16 O+ 16 O molecular states (and hence the superdeformed states of 32 S).…”
Section: Introductionmentioning
confidence: 99%